Concurrent Klebsiella pneumoniae liver abscess and infective endocarditis: A rare case report and literature review - Yuanwen Chen; Yisheng Zhou; Zhibin Xu (IDCases)
Background: Investigating the clinical characteristics and treatment strategies of pyogenic liver abscess (PLA) complicated by infective endocarditis (IE), this study draws on a successfully treated case of PLA caused by Klebsiella pneumoniae, alongside a literature review of similar cases. Case Summary: We report a 50-year-old male with type 2 diabetes who presented with acute fever, chills, and a liver abscess. The patient was initially treated with intravenous ceftriaxone (2 g daily). Due to the onset of septic shock, the antibiotic regimen was escalated to piperacillin-tazobactam (4.5 g every 8 h) and levofloxacin (0.5 g daily). Ultrasound-guided percutaneous drainage of the liver abscess was performed, and blood cultures confirmed Klebsiella pneumoniae. Upon the development of infective endocarditis, the treatment was adjusted to a combination of ceftriaxone and amikacin for one week, followed by six weeks of ceftriaxone monotherapy, resulting in full recovery. Conclusion: This case report illustrates the rare association of Klebsiella pneumoniae-induced PLA with IE in a diabetic patient. It emphasizes the importance of individualized treatment strategies, with insights drawn from this case contributing to the understanding of managing such complex infections. While the successful outcome of this case provides valuable clinical insights, it highlights the need for careful consideration in treatment approaches. The findings from this single case should guide clinicians in similar scenarios but should not be generalized without further evidence.